- Mengoptimalkan Kinerja: Investigasi Pengaruh Kepuasan Kerja, Kompensasi, dan Motivasi terhadap Kinerja Pegawai - Putra, Feby Arma; Kurniati, Deti (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to ascertain how employee performance in Serang City is impacted by motivation, pay, and job satisfaction. This study employs correlational quantitative research methodology. Using data collected from the field, quantitative research aims to test theories that have been produced. There were 96 responders in the sample. A variance-based structural equation test or a partial least square-structural equation model (PLS-SEM) were used in this study's inferential analysis. The study's findings indicate that: 1). Motivation has a positive and significant impact on job satisfaction; 2). Compensation has a favorable impact on job satisfaction; 3). Employee performance is positively influenced by motivation; and 4). Employee performance is greatly impacted by compensation, 5). Managing Worker Satisfaction Improves Employee Performance Keyword: compensation, motivation, job satisfaction, employee performance